2023
DOI: 10.9734/afsj/2023/v22i6638
|View full text |Cite
|
Sign up to set email alerts
|

Development and Organoleptic Evaluation of Vegan Honey Tender Bamboo Shoots Murabba

Abstract: The aim of this study was to make a Bamboo Shoots (Phyllostachys edulis) are regarded as one of the beneficial health foods due to their high protein, carbohydrate, vitamin, fiber, and mineral composition and very low fat content. In the current study, "Value of tender bamboo shoots murabba with cinnamon, cardamom, lemon, vegan honey, jaggery," vegan honey bamboo murabba was made in the food science and technology laboratory of the department of food and nutrition at Babasaheb Bhimrao Ambedkar University in Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Devi and Singh [6] showed that the soluble protein content in fermented buds increased from 3.1% to 7.8% and 8.1% on the third and fifth day of fermentation, respectively. In another study by Agrahar-Murugkar and Subbulakshmi [7], fermented bamboo lungs were found to have better nutritional value (8.5%) in terms of protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Devi and Singh [6] showed that the soluble protein content in fermented buds increased from 3.1% to 7.8% and 8.1% on the third and fifth day of fermentation, respectively. In another study by Agrahar-Murugkar and Subbulakshmi [7], fermented bamboo lungs were found to have better nutritional value (8.5%) in terms of protein content.…”
Section: Introductionmentioning
confidence: 99%